Ultrastabilization of Zeolite Y Transforms Brønsted–Brønsted Acid Pairs into Brønsted–Lewis Acid Pairs. Issue 43 (26th September 2018) - Schroeder, Christian; Hansen, Michael Ryan; Koller, Hubert
Abstract: Two pairs of Brønsted acid sites have been identified in H, Na‐Y zeolite, located in the supercage and in the sodalite cage, which upon ultrastabilization (dealumination) are transformed into pairs of Brønsted and Lewis acid sites. This mild postsynthetic modification step is an important process for converting this material into an active catalyst for large‐scale commercial reactions. Pairing structures and their transformations have been investigated using 1 H double‐quantum NMR spectroscopy experiments for dehydrated zeolite, H, Na‐Y, and its ultrastabilized form, H, Na‐USY. This approach enables the detection of pairs of Brønsted and Lewis acid sites with unprecedented 1 H resolution and distinguishing them from isolated acid sites. The dealumination is also detected by static 27 Al solid‐state NMR experiments. Abstract : Neighboring active sites : Zeolite Y exhibits two different pairs of Brønsted acid sites in the d6r and the sod units, which are transformed into Brønsted–Lewis acid pairs upon ultrastabilization. Modern 1 H and 27 Al solid‐state NMR spectroscopy techniques allow a substantial increase in signal resolution and acquisition of very broad lines. Thus, the structural information on catalytic sites of zeolites is further augmented.